The Maya Tropical Forest People, Parks, and Ancient Cities - Nations, James D. (University of Texas Press, 2021)
The Maya Tropical Forest, which occupies the lowlands of southern Mexico, Guatemala, and Belize, is the closest rainforest to the United States and one of the most popular tourist destinations in the Western Hemisphere. It has been home to the Maya peoples for nearly four millennia, starting around 1800 BC. Ancient cities in the rainforest such as Palenque, Yaxchilan, Tikal, and Caracol draw thousands of tourists and scholars seeking to learn more about the prehistoric Maya. Their contemporary descendants, the modern Maya, utilize the forest's natural resources in village life and international trade, while striving to protect their homeland from deforestation and environmental degradation. Writing for both visitors and conservationists, James Nations tells the fascinating story of how ancient and modern Maya peoples have used and guarded the rich natural resources of the Maya Tropical Forest. He opens with a natural history that profiles the forest's significant animals and plants. Nations then describes the Maya peoples, biological preserves, and major archaeological sites in Mexico, Guatemala, and Belize. Drawing on more than twenty-five years of conservation work in the Maya Tropical Forest, Nations tells first-hand stories of the creation of national parks and other protected areas to safeguard the region's natural resources and archaeological heritage. He concludes with an expert assessment of the forest's future in which he calls for expanded archaeological tourism to create an ecologically sustainable economic base for the region